Autonomic response of older women to the submaximal effort in the six-minute walk test: a cross-sectional study (Fisioterapia e Pesquisa, 2022)
This cross-sectional study aimed to evaluatethe autonomic response of older women in the six-minutewalk test. In total, 32 women aged 60 years or older withouta diagnosed health problem were evaluated during the sixminute walk test. To monitor the autonomic response, thefollowing variables were considered: heart rate, systolic anddiastolic blood pressure, respiratory rate, and perceivedexertion. These variables were compared during rest,effort, and recovery. This study also sought a correlationbetween autonomic function variables and performancein the test and perceived exertion. Results showed that theeffort made by older women in the six-minute walk testinduces an autonomic response resulting in increased heartrate and systolic and diastolic blood pressure; however,the respiratory rate remained unchanged during the test.Diastolic blood pressure remained high during recovery.No correlation was found neither between perceivedexertion and cardiovascular physiological response norbetween distance covered and variation of the autonomicresponse or level of physical conditioning. Therefore,the effort spent in the six-minute walk test promotesan autonomic response in older women, increasingcardiovascular stress without increasing ventilation.In this context, the Borg scale was not representative ofcardiovascular stress during the test.